The role of the Association of Persons with Disabilities in protecting persons with disabilities - Fayziyev O‘rinboy Toshmuhammad o‘g‘li (Genius Journals, 2025)
This article examines the establishment and activities of the Association of Persons with Disabilities, its role in protecting the rights of persons with disabilities, as well as the current challenges faced by persons with disabilities in Uzbekistan and potential solutions to these issues.
Keywords: Convention; Association of Persons with Disabilities; Persons with Disabilities